Ideology and Translation - BENNOUDI , Hanan; Zaid, Abdelali (International Journal of Language and Literary Studies, 2023)
Ideally, a translation should be faithful to the original message making the translator invisible; however, myriad factors come into play to reconstruct the text suiting the patronage agenda and thus put the translator into the visible mode as he/she rewrites the text. This article explores, in-depth, the concept of Ideology in translation. In other words, to what extent may Ideology impact the translator’s choices regarding what to add and/or omit and other strategies that, consequently, shape the receivers’ worldviews? Having in mind the importance of ideology and translational changes, myriad examples are provided within the theoretical and practical parts to scrutinize the existence of the manipulation within.